JAVANESE PHONOLOGICAL INTERFERENCE IN ENGLISH PRONUNCIATION OF ENGLISH LITERATURE DEPARTMENT STUDENTS - Siqoyah, Surotun; Latifah, Nur (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
The occurrence of phonological interference can be found if the native is able to acquire multilingually. The research aims to reveal the phonological aspects causing phonological interference and establish the strategies for avoiding interference. Students of the English literature department that take English Language Teaching (ELT) and speak Javanese, Indonesia, and English language become the primary sources of this research. The method used in this research is a descriptive qualitative as research design and the theory of Geoffry S. Nathan for the analysis. Meanwhile, Marsono’s theory is employed to compare it with vocal, diphthong, and consonant in Javanese language. The finding shows that phonological interference comes from a segmental aspect, totaling errors up to 99 and 189 in the suprasegmental aspect. In the segmental aspect, errors of English pronunciation were found on the assimilation of speech implementation based on vowel, diphthong, and consonant. Meanwhile, in the suprasegmental aspect, word stress on the second syllable with two, three, and four-syllable words become the most errors. Therefore, phonological interference can be avoided by doing more individual practice in looking for difficult vocabularies and using English as the main language in doing enjoyable activities such as listening to music and watching movies.